Women with Metabolic Syndrome and General Obesity Are at a Higher Risk for Significant Hyperuricemia Compared to Men - Kim, In Young (J Clin Med, 2019)
Hyperuricemia is an emerging potential biomarker for metabolic syndrome (MetS) and its complications. This study aimed to investigate the risk factors of hyperuricemia, particularly, the association of hyperuricemia with MetS and general obesity according to sex. We performed multivariate logistic regression analyses using the 2016 Korean National Health and Nutrition Examination Survey data. Hyperuricemia was defined by a serum uric acid level ≥7.0 mg/dL for men and ≥6.0 mg/dL for women. General obesity was based on a body mass index (BMI) ≥25 kg/m(2). Among a total of 5591 Korean adult participants, 685 (12.3%) individuals had hyperuricemia. Hyperuricemia was significantly associated with MetS in men (odds ratio (OR): 2.38, 95% CI: 1.84–3.08) and in women (OR: 4.15, 95% CI: 2.75–6.28) after adjustments. General obesity was also independently related to hyperuricemia in both sexes (OR: 2.17, 95% CI: 1.76–2.68 in men, OR: 3.80, 95% CI: 2.82–5.12 in women). In subgroup analyses, the presence of concomitant MetS and general obesity posed a strikingly higher risk for hyperuricemia among women (OR: 7.24, 95% CI: 4.56–11.50) when compared to men (OR: 2.90, 95% CI: 2.12–3.96). More attention should be paid to the increased risk of hyperuricemia for females with both MetS and general obesity.